Effectiveness of Objective Structured Practical Examination as an Assessment Method for Indian Medical Graduates: A Pilot Project Carried Out in Pathology at a Medical College in Western India - Patel, Nidhi Rajiv; Shah, Rupal Jaymin; Prajapati, Akanksha (Annals of Pathology and Laboratory Medicine, 2024)
Background Practical assessment plays a vital role in medical education. Traditional Practical Examination (TPE) assesses only the knowledge of students without providing constructive feedback. The Objective Structured Practical Examination (OSPE) is a structured, objective, and unbiased tool for assessment. It evaluates all domains of Miller's pyramid with a few limitations. This study assesses the effectiveness of OSPE compared to TPE for second-year MBBS students in Pathology practical exams as an assessment tool in our hospital settings. It also aims to analyze the perceptions of students and faculty regarding OSPE. Material and Methods A hospital-based prospective study was conducted during internal practical exams of second-year MBBS students in the Pathology department of a tertiary care hospital, Ahmedabad, Gujarat, India. A total of 115 students and 13 faculty members were enrolled. After a sensitization session, OSPE was conducted alongside traditional exams with the same set of faculty at the same time in the same lab. Feedback was collected from both students and faculty. Marks obtained and perceptions of both methods were compared. Results The marks obtained by students using TPE and OSPE had a median of 12.5 with an IQR of 3 and a median of 15 with an IQR of 2, respectively. The p-value was highly significant, suggesting better marks scored by students in OSPE. According to students' perceptions, the majority felt that OSPE is better, well-structured, unbiased, and less stressful compared to TPE. Most faculty members also gave positive feedback for OSPE. Conclusion Both students and faculty have a positive approach towards OSPE as it assesses almost all types of practical skills with the ability to provide feedback. It reduced stress and allowed students to achieve higher marks. They recommended OSPE in the formative assessment of medical students.